Morphologic and genetic characterization of Sarcocystis sp. from the African grey parrot, Psittacus erithacus, from Costa Rica - Dubey, J.P (2006)
A species of Sarcocystis is reported from a naturally infected African grey parrot, Psittacus erithacus, from Costa Rica. Only mature sarcocysts, measuring up to 2 mm in length and up to 750 μm in width, were observed. The sarcocyst wall was smooth. The villar protrusions on the sarcocyst wall were up to 5 μm long and up to 1.1 μm wide; they were folded over the sarcocyst wall giving a thin-walled appearance. The microtubules in villar protrusions were smooth and confined to villar protrusions. Bradyzoites in sections were 5.4ñ6.6 × 1.3ñ2.0 μm in size. Sequencing the small subunit and first internal transcribed spacer portions of ribosomal DNA related this parasite to, but distinguished it from, previously characterized species of Sarcocystis that encyst in the musculature of birds and complete their sexual development in New World opossums of the genus Didelphis. This evidence suggests that the parrot may have acquired its infection from an opossum from which it suffered a debilitating attack a year prior to the onset of depression, anorexia, and ultimately death.